Peran Sekolah Adiwiyata dalam Meningkatkan Kesadaran Lingkungan Generasi Muda di sekolah terpencil - Rabiah Tul Al Adawiah Sujarniawan; Ellianawati Ellianawati; Bambang Subali (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
Environmental awareness is an important value that should be instilled in young generations to address increasingly complex environmental issues. Schools play a significant role in developing environmentally responsible character through the Adiwiyata Program. This study aims to analyze the role of Adiwiyata Schools in improving environmental awareness among young people using a literature review method by examining various journals, books, and related documents.The results indicate that the Adiwiyata Program effectively enhances students' environmental knowledge, attitudes, and behaviors through environmentally oriented school policies, environmental-based curricula, participatory activities, and eco-friendly facilities management. The program encourages positive habits such as proper waste disposal, energy conservation, recycling, and maintaining school cleanliness. Therefore, the Adiwiyata Program contributes to developing a generation that is environmentally aware and responsible for environmental sustainability.